Retroflexion in South Asia: Typological, genetic, and areal patterns - Arsenault, Paul (Journal of South Asian languages and linguistics, 2017)
Retroflexion in South Asia has been the subject of at least two previous typological studies: (1969. Toward a phonological typology of the Indian linguistic area. In T. A. Sebeok (ed.), , 543–577. Paris: Mouton) and Tikkanen (1999. Archaeological-linguistic correlations in the formation of retroflex typologies and correlating areal features in South Asia. In Roger Blench & Matthew Spriggs (eds.), , 138–148. London & New York: Routledge). Despite their many virtues, these studies are limited by the size of their data samples, their dependence on qualitative data without quantitative analysis, and their use of hand-drawn maps. This paper presents the results of an entirely new survey of retroflexion in South Asia – one that incorporates a larger language sample, quantitative analysis, and computer-generated maps. The study focuses on the genetic and geographic distribution of various retroflex subsystems, including retroflex obstruents, nasals, liquids, approximants and vowels. While it is possible to establish broad statistical correlations between specific types of contrast and individual language families (or sub-families), the study finds that the distribution of most retroflex systems is more geographic in nature than genetic. Thus, while retroflexion is characteristic of South Asia as a whole, each type of retroflex system tends to cut across genetic lines, marking out its own space within the broader linguistic area.